2020
DOI: 10.3389/fpsyg.2020.615746
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Rank of the Competition as a Factor Differentiating Between the Affective States of Swimmers and Their Sport Performance

Abstract: PurposeThe aim of the study was to establish the differences in affective states of swimmers depending on the subjective rank of the competition and the relationship between affective states and performance in sports competitions of low, medium and high subjectively perceived rank.MethodsThe respondents (n = 31) aged from 15 to 23 years (18.1 ± 2.397) were studied using the psychological questionnaires Perceived Stress Scale (PSS-10), Profile of Mood State (POMS), and Positive and Negative Affect Schedule (PAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
1
1
1
Order By: Relevance
“…The tension factor showed significant differences in the overall analysis, while the values obtained were lower than those provided by other research (10.21 ± 5.56 AU vs. 12.94 ± 6.228) [26]. The significant differences in the depression factor between week 1 and 10, when the values decreased, could be due to the positive effect of the athletes returning to training and being able to interact again with their coaches and teammates [27].…”
Section: Discussioncontrasting
confidence: 61%
“…The tension factor showed significant differences in the overall analysis, while the values obtained were lower than those provided by other research (10.21 ± 5.56 AU vs. 12.94 ± 6.228) [26]. The significant differences in the depression factor between week 1 and 10, when the values decreased, could be due to the positive effect of the athletes returning to training and being able to interact again with their coaches and teammates [27].…”
Section: Discussioncontrasting
confidence: 61%
“…Samełko et al [ 21 ] showed that depression and positive emotional state were predictive of outcome in high and mid-range competitions. In turn, Monteiro et al [ 22 ] found that the most important reason for attrition from the sport was dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Outro fator que influencia o atleta a negar sua condição é a pressão que a sociedade exerce sobre ele, visto que sua imagem perante a sociedade é de um individuo com saúde física e mental e que sempre deve apresentar um desempenho acima da média, até mesmo para garantir seu lugar na equipe esportiva(43).Em um estudo com nadadores, onde foi avaliado o desempenho esportivo, o nível de depressão foi um preditor negativo significativo dos resultados esportivos obtidos durante competições. Foi possível observar que o fator psicológico do atleta, em especial a depressão, é um fator particularmente importante na determinação do resultado esportivo(44).Os fatores mais comuns da depressão nos atletas são: personalidade do atleta, ansiedade, baixa autoestima, fracasso, lesão física, mudanças de comportamento, autocobrança, problemas afetivos, perda de prestígio ou da posição de titular, baixo rendimento. Assim, um atleta com depressão pode apresentar rendimento esportivo prejudicado, desempenho abaixo da expectativa, diminuição da dedicação aos treinos, aumento da frequência do lesões, isolamento em relação aos companheiros e transtornos mentais(43).…”
unclassified